Choreographing the everyday feast: accommodating Malaysian temporary markets in a changing context - Zakariya, Khalilah; Ware, SueAnne; Helsel, Sand (CG Publisher, 2012)
Temporary markets are often perceived as places that possess a sense of localness. They may seem to exist on spontaneity and chaos, but in fact rely on certain infrastructures and conditions that enable them to operate. However, as developments continue to progress in cities and suburbs, there will be inevitable changes in lifestyle, mobility and values of public spaces. Temporary markets will be, if they are not already, under pressure from the processes of urbanisation. With these changes expected to happen, how can temporary markets continue to develop with their rich experiential qualities? This paper explores strategies to accommodate prospective temporary markets in Putrajaya, Malaysia, given the condition that the markets are temporary and will have to be relocated in the future. The study employed techniques of observation, mapping, personal experiences and speculative design propositions to understand and test different ways of how the markets might operate in a changing context. The findings revealed that the operations of temporary markets need to be adapted to its context, through choreographing the flows of its spaces, users and activities, and the provision of specific hard and soft infrastructures. The planning of a market involves strategies at multiple scales.